A historical perspective on unconfined seepage: correcting a common fallacy. Issue Volume 172:Issue EH 2(2019:May) (24th April 2019) - Wesley, Laurence D; Preene, Martin
Abstract : It is commonly assumed in seepage studies for geotechnical problems that the phreatic surface (the line of zero pore water pressure) represents the upper flow line and is the boundary of the seepage zone. Seepage is assumed to occur below the phreatic surface but not above it (this is termed the 'phreatic assumption'). A brief historical review is given of the development of seepage theory and how this assumption became established. It is explained that this assumption is true only if the soil involved is coarse grained when the majority of the pore water above the phreatic surface will drain out of it under gravity forces. The assumption is not valid for fine-grained soils such as clay, in which case water is held in the soil pores by capillary forces for many metres above the phreatic surface and seepage occurs above the phreatic surface according to the same laws as below it. Examples are given of correct flow nets for unconfined seepage in clay compared with those routinely adopted in soil mechanics.